Clinical implications of heat shock protein 70 in oral carcinogenesis and prediction of progression and recurrence in oral squamous cell carcinoma patients: a retrospective clinicopathological study - Heba A. Elhendawy (European Journal of Medical Research, 2023)
Abstract Background Oral cancer is a common cause of death worldwide. The search for novel biomarkers for oral cancer is an ongoing struggle. Prognostic biomarkers are of great importance in diagnosis, and prediction of the cancer outcome. There are several disagreements in oral cancer studies over the role of heat shock proteins as prognostic markers. The current study investigated HSP70 expression in diverse tissues ranging from normal oral mucosa to dysplastic oral epithelium and oral squamous cell carcinoma to determine its role in oral carcinogenesis. Moreover, HSP70 was evaluated concerning different prognostic parameters to determine its capability in predicting cancer progression. Recurrence of tumor was recorded, and patients` disease-free survival was calculated and analyzed considering HSP70 expression to determine the potential utility of HSP70 immuno-expression in predicting recurrence. Methods A retrospective study was accomplished on 50 cases of OSCC. Biopsies from the cancerous tissue, the free surgical margin, and the normal oral mucosa were used. The grading of dysplastic epithelium and OSCCs followed the criteria of WHO classification (2017). The clinicopathological and follow-up records for each patient were retrieved. Pearson’s Chi-square test, one-way ANOVA, and post hoc tests were used to analyze the variance of HSP70 immuno-expression concerning different parameters. The Kaplan–Meier method was used to compute and visualize disease-free survival, and the log-rank test was used to analyze the data. With Cox regression, univariate and multivariate survival analyses were run. A P-value of 0.05 or less was regarded as statistically significant. Results A significant increased expression of HSP70 was observed as the tissue progressed from normal to dysplastic epithelium, and carcinoma (P = 0.000). HSP70 revealed a significant increased expression by progression from mild to severe dysplasia (P = 0.023), and also from well to moderately and poorly differentiated carcinoma (P = 0.000). High HSP70 immuno-expression was significantly associated with progression of OSCC; large-sized tumors (P = 0.002), advanced TNM clinical stages (P = 0.001), positive nodal involvement (P = 0.001), presence of recurrence (P = .008), and reduced DFS (P = 0.014). Conclusion HSP70 has a crucial contribution to oral carcinogenesis, and its immune-expression could potentially be used as predictor of progression and recurrence of OSCC patients. Trial registration: Retrospectively registered.